Mechanisms of unconventional CD8 Tc2 lymphocyte induction in allergic contact dermatitis: Role of H3/H4 histamine receptors - Alcain, Julieta; Infante Cruz, Alejandra del Pilar; Barrientos, Gabriela; Vanzulli, Silvia; Salamone, Gabriela; Vermeulen, Mónica (Frontiers in Immunology, 2022)
Histamine (HIS) is a potent mediator, which plays a central role in inflammation and allergy, acting through four G-protein coupled receptors (H1R – H4R). It is an accepted promoter of type 2 immunity in CD4+ T cells during hypersensitivity. Previously, we demonstrated that HIS can promote antigen cross-presentation inducing the activation of antigen specific CD8+ T cells in an asthmatic murine model. Non-classical CD8+ T cell profiles, such as Tc2 or Tc17, are associated with allergic disease persistence and chronicity. In this paper we focus on the role of the H3 and/or H4 receptors in the development of allergic contact dermatitis. We were able to show that induction of the type 2 profiles associated to IL-13 production both by CD4 and CD8 lymphocytes, depend of the interaction of HIS with H3 and H4 receptors. Blocking both receptors using the H3/H4R-selective antagonist thioperamide or the selective H4R ligand H4 JNJ777120 reduces the inflammatory response, inducing an immunosuppressive profile associated with the increased proportion of FOXp3+ regulatory T lymphocytes and CD11b+GR1+ myeloid suppressor cells. Interestingly, only H4 blockade on dendritic cells is capable of modulating most of the inflammatory effects observed in our model, which does not apply to H3R.